Predictors and outcomes of patients requiring repeat transvenous lead extraction of pacemaker and defibrillator leads. Issue 2 (24th January 2018) - Claridge, Simon; Johnson, Jonathan; Sadnan, Gazi; Behar, Jonathan M.; Porter, Bradley; Sieniewicz, Benjamin; Jackson, Tom; Webb, Jessica; Gould, Justin; Sohal, Manav; Hamid, Shoaib; Patel, Nik; et al.
Abstract: Background: A proportion of patients who undergo an initial lead extraction procedure will require a second, repeat extraction. Data regarding this clinical entity are scarce and neither the predisposing risk factors for, nor outcomes from, these procedures have been described previously. We sought to determine the incidence, risk factors, and outcomes of repeat lead extraction. Methods: A database of extraction procedures from 2001 to 2015 was analyzed. Repeat extraction procedures were identified and the indication for extraction was dichotomized into infection and lead‐related problems. Univariate and multivariate analyses were performed to identify predictors of repeat extraction. Results: 807 extraction procedures were identified in 755 patients of whom 6% required a repeat extraction. At multivariate analysis, only suffering a major complication at the initial extraction procedure (odds ratio [OR] 21.5, 95% confidence interval [CI] 2.69–171.92; P < 0.01), complexity of device (cardiac resynchronization devices/implantable cardioverter defibrillators) (OR 2.58, 95% CI 1.2–5.2; P = 0.01), and age (OR 1.02 per year, 95% CI 1.0–1.4; P  =  0.03) were significant predictors of repeat extraction. When repeat extraction was required for infection there was a significant increase in mortality compared with those who did not require a second procedure (36% vs 23%; P  =  0.02). Conclusions: Repeat lead extraction is required in 6% of cases. Complexity of device, age at extraction, and a major complication at the first extraction were predictors of repeat extraction. Mortality is significantly increased where the repeat procedure is for infection. Clinicians should alert patients to the potential need for further extraction and the increased risks of repeat procedures when indicated for infection.